Analysis of Cooperative Health Level Based on Minister of Cooperatives and Small and Medium Enterprise Regulation Number 9 of 2020 - Wibowo, Tri Joko Ari; Hambani, Susi; Hutomo, Yoyo Priyo (Institut Bisnis dan Informatika Kesatuan, 2024)
This study analyzes the health level of the Sharia Savings and Loans and Financing Cooperative ABC based on the Regulation of the Minister of Cooperatives and SMEs Number 9 of 2020. The focus of the study is on the financial performance and capital aspects for the period 2021-2023. The data were analyzed using the cooperative health inspection worksheet guidelines according to the Regulation of the Minister of Cooperatives and SMEs Number 15 of 2021. The results of the study show that Sharia Savings and Loans and Financing Cooperative ABC has been in the Under Special Supervision category for three consecutive years. The financial performance aspect shows a decrease in profitability and operational efficiency, while the capital aspect records a relatively good capital adequacy ratio. However, there are significant challenges in the liquidity and credit risk management aspects, including an increase in problem receivables. This study recommends strengthening risk management, increasing operational efficiency, and developing capital strategies to support the sustainability of cooperatives. These findings are important for cooperative managers, members, and policy makers in improving the health of sharia cooperatives in Indonesia.